2018
DOI: 10.22146/ijg.36263
|View full text |Cite
|
Sign up to set email alerts
|

Participatory implementation within climate change related policies in urbanized area of Indonesia

Abstract: Geographically, Indonesia has been subjected towards various climate change related phenomena. This research aim at evaluation of participatory implementation towards climate change related policy which has been set in Indonesia. The research method derived from qualitative framework developed by UNESCO. The research took RAN-API or National Action Plan upon Climate Change Adaptation which has been established since 2013. The document has been integrated within National Medium Term Plan launched at 2015 up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…is is summarized in Figure 4. A study by (Suarma et al 2018) on the importance of participatory implementation within climate change-related policies in Indonesia revealed that the participatory method effectively evaluates climate changerelated policies. Community participation from government, private sector, and local communities should be included in the program evaluation, to build a strong trust, effectiveness, and fairness of a program that leads to a successful program or policy.…”
Section: E Proposed Future Framework For Research and Developmentmentioning
confidence: 99%
“…is is summarized in Figure 4. A study by (Suarma et al 2018) on the importance of participatory implementation within climate change-related policies in Indonesia revealed that the participatory method effectively evaluates climate changerelated policies. Community participation from government, private sector, and local communities should be included in the program evaluation, to build a strong trust, effectiveness, and fairness of a program that leads to a successful program or policy.…”
Section: E Proposed Future Framework For Research and Developmentmentioning
confidence: 99%
“…Due to the vulnerability of this position, the Government of Indonesia appointed Bandar Lampung, along with Semarang City, Pekalongan City, Blitar City, Tarakan City, Malang Regency, Batu City, and Malang City, as one of the pilot areas for implementing the National Action Plan for Climate Change Adaptation (RAN-API) [10][11][12]. Due to their vulnerability, these areas are being targeted to become pilot cities in Indonesia through the implementation of a series of governance measures aimed at achieving an adaptive and climate change resilient city.…”
Section: Introductionmentioning
confidence: 99%